Some Approaches to the Development of the Management Control Concept - MULLAKHMETOV, Khanif Sharifzуanovich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
Characteristics of the environment of functioning and development of the organization, namely the increasing complexity (presence of a number of factors of internal and external environment that influence the activity of the organization), dynamism (factors that significantly affect the organization, change quickly and are interconnected) and uncertainty (as a consequence of the two previous characteristics), as well as qualitative changes in the society, require new approaches, systems, technologies and management practices. Accordingly, the management structure and management processes as a whole, as well as individual management subsystems and their characteristics should change. The aim of this work is to develop common approaches to developing the concept of control in modern conditions, which could serve as a basis for creating and maintaining an effective system of management control in organizations. To achieve the goal, the author proposes the concept of control based on theoretical and practical knowledge in management, while seeing control as one of the subsystems and the basic functions of management. Standardization and analysis of managerial situations allowed the author to specify the role of the control and determine the actions of management at various stages of the management process. A systematic approach to the organization of the control and consideration of organizations as open systems provided the opportunity to use the concept of controlling in the work, which suggests a fundamentally different approach to the evaluation of deviations in the activities of organizations; nevertheless, the conclusions drawn for deterministic situations have significant practical importance as the basic provisions for a further analysis of administrative situations in the face of uncertainty. One result of the study is a model and an algorithm of management control activities suggested by the author, based on a systematic approach to management and control processes and existing practice, taking into account the influence of environmental factors and the internal potential of the organization.
Keywords: management process, management situation, concept of control, algorithm of control, management control